Psychological Contract: A Systematic Literature Review - Dina Safitri (International Journal of Scientific Multidisciplinary Research, 2024)
English abstract only consisted of one paragraph This comprehensive study thoroughly examines the psychological contract literature by reviewing 134 papers published from 1989 to 2022. It extensively explores various aspects, including the conceptual framework, classifications, influencing factors, measurement criteria, and evolutionary trends of psychological contracts. Through a critical analysis, this paper reveals that certain areas within the realm of psychological contracts have reached a saturation point, with a wealth of existing research. It highlights the need for a paradigm shift towards studies conducted from the employer's standpoint, which can offer invaluable insights into the dynamics of psychological contracts. In essence, this review encapsulates the existing knowledge on psychological contracts and maps out a roadmap for future research, emphasizing the importance of diverse perspectives and methodological approaches